Food Security Policy Business Plan Model: Case Study of Food Security Policy Implementation Network in South Sulawesi Province - Rulinawaty; Lukman Samboteng; M.Rachmat Kasmad; Mutmainnah Basit (JOM, 2024)
This study analyses the Food Security Policy Business Plan Model through a case study of its implementation in South Sulawesi Province. This research highlights the model's success in strengthening food security through five main elements: identification of local potential, production and distribution plans, strategic partnerships, risk management, and monitoring and evaluation. The research method involves collecting data through in-depth interviews with policy stakeholders, entrepreneurs, and members of policy implementation networks. Data was also obtained through participatory observation and analysis of policy-related documents. Data analysis was carried out using a thematic approach to identify patterns of findings that emerged from the qualitative data. The research results positively impact food system efficiency, fostering cross-sector collaboration and increasing local economic resilience. However, the findings also highlight challenges that still need to be addressed, especially in the context of external risk management. This research makes a valuable contribution to understanding the dynamics of food security policy implementation at the regional level. It provides a basis for developing more effective policies in the future.